The Ice Cave A Woman's Adventures from the Mojave to the Antarctic - Jane Bledsoe, Lucy (The University of Wisconsin Press, 2006)
For Lucy Jane Bledsoe, wilderness had always been a source of peace. But during one disastrous solo trip in the wintry High Sierra she came face to face with a crisis: the wilderness no longer felt like home. The Ice Cave recounts Bledsoe's wilderness journeys as she recovers her connection with the wild and discovers the meanings of fear and grace. These are Bledsoe's gripping tales of fending off wolves in Alaska, encountering UFOs in the Colorado Desert, and searching for mountain lions in Berkeley. Her memorable story "The Breath of Seals" takes readers to Antarctica, the wildest continent on earth, where she camped out with geologists, biologists, and astrophysicists. These fresh and deeply personal narratives remind us what it means to be simply one member of one species, trying to find food and shelter-and moments of grace-on our planet.